TRAVERSING THE ACADEMIC PERFORMANCE OF CULTURE AND THE ARTS MEMBERS - Tabao, Kristel Joy (International Journal of Arts, Sciences and Education, 2022)
A good education in the arts is built on and reflects recognition of the specific and unique manner that people's thinking is shaped by the arts, as well as the way that the arts shape people's lives. This study intends to relate the academic performance of members of the Culture and the Arts organization at Cagayan State University to the problems they faced in their academic pursuits. In this study, a quantitative approach to research design was taken. When asked whether or not participation in any culture and the arts performances helps learners succeed academically, coaches and trainers unequivocally confirmed that it does have a major effect on the learners' academic performance. However, there were those within the academic community who held the view that students' participation in cultural and artistic performances hampered their ability to achieve academic success. They reasoned that this was due to the fact that students who participated in cultural and artistic performances spent less time inside the classroom and on their studies because their schedules often clashed with those of their other obligations, such as rehearsals, competitions, and so on. The situations that individuals face as performers and artists have little bearing on their capacity to do academic work, despite the fact that they actually experience those circumstances.